Influence of clinical learning environment on caring and advocacy among Omani undergraduate nursing students: a cross-sectional survey - Valdez, Glenn Ford D.; Nashwan , Abdulqadir J.; Inocian , Ergie Pepito; Cayaban , Arcalyd Rose R.; Turingan , Oscar M.; Al Nasiri, Yusra (Universitas Airlangga, 2026)
Introduction: Nursing students gain clinical skills and shape professional behaviors through ongoing education. As Oman updates its nursing education to match healthcare demands, examining how clinical environments impact students' compassion and advocacy is vital. This study assessed the effect of clinical settings on undergraduate nursing students' caring and advocacy behaviors. Methods: This cross-sectional, quantitative study used adapted tools, including an author-developed nursing student advocacy (NSA) scale, the clinical learning environment inventory (CLEI-42), and the caring behaviors inventory-24 (CBI-24). Stratified sampling based on university, year, and age selected 461 Bachelor of Science in Nursing students, proportional to each subgroup (CL.95, CI-0.5). Descriptive and inferential statistics, such as Pearson ’scorrelation, were used to assess the relationships among demographics, clinical learning environment, caring behaviors, and advocacy behaviors. Results: The primary study variables in the clinical learning environment, caring behavior inventory, and nursing advocacy scale showed a significant correlation between the clinical learning environment and caring behaviors (r=0.388, p<0.001) and a significant correlation between the clinical learning environment and nursing advocacy and right-seeking behaviors (r=0.634, p<0.001). Conclusions: A considerable positive moderate relationship exists between the clinical learning environment and caring behaviors, and a substantial positive moderate relationship exists between nursing advocacy and caring behavior.